Characterization of the deployment process of a space antenna prototype - Lee, Yeow Kok (2015)
Smart materials have been researched and made used of in many applications in our everyday lives. Their use in space technology proved to be highly practical as the high cost of material can be compensated by their unique functions needed in such operations. Shape memory alloys, a kind of smart material, have been found to be highly effective in providing actuation. Using it as an actuator, previous Final Year Project students have come up with a prototype of a deployable antenna that deploys by itself when heated by the sun in orbit. The prototype could not deploy on its own on Earth due to its own weight. The author researched on various ways to simulate micro-g deployment tests, and considering feasibility and cost, decided and proceeded to testing the prototype using helium as the suspension medium to offset the weight of the antenna petals. The deployment tests proved to be successful. Various components of the prototype design were analyzed for their performance after the deployment test. Calculations and improved designs were made on them. The author collaborated with other FYP students on improving the overall design of the antenna, focusing on deployability to be reported in this report.